Behaved instability: public debt and institutional investors in Brazil - Damásio, Kevin Luís (Departamento de Economia, 2018)
This article aims to investigate the economic implications of the participation of institutional investors in the context of the brazilian market. Therefore, the valuation positions maintained by these players in relation to the composition of their investment portfolios should be observed. It is prudent to note that the portfolio of these agents is constrained by the increase of deadlines and the weighting of greater risks, given the process of valuation attraction given by the brazilian public debt situation. The guarantee of access to papers that combine liquidity, profitability and relative low risk with public debt, constrains institutional investors to seek value gains in projects such as financing of long-term investments in new industrial plants and capital goods. On the other hand, it is indicated that this conservative behavior of the institutional investors helps in the prevention of large speculative movements in the brazilian market, conducting us to reinterpret the analysis of the hypothesis of Minsky's financial instability having in account the specificities of the Brazilian case.